Protein folding modulates the swapped dimerization mechanism of methyl-accepting chemotaxis heme sensors. - Marta A Silva (PLoS ONE, 2012)
The periplasmic sensor domains GSU0582 and GSU0935 are part of methyl accepting chemotaxis proteins in the bacterium Geobacter sulfurreducens. Both contain one c-type heme group and their crystal structures revealed that these domains form swapped dimers with a PAS fold formed from the two protein chains. The swapped dimerization of these sensors is related to the mechanism of signal transduction and the formation of the swapped dimer involves significant folding changes and conformational rearrangements within each monomeric component. However, the structural changes occurring during this process are poorly understood and lack a mechanistic framework. To address this issue, we have studied the folding and stability properties of two distinct heme-sensor PAS domains, using biophysical spectroscopies. We observed substantial differences in the thermodynamic stability (ΔG = 14.6 kJ.mol(-1) for GSU0935 and ΔG = 26.3 kJ.mol(-1) for GSU0582), and demonstrated that the heme moiety undergoes conformational changes that match those occurring at the global protein structure. This indicates that sensing by the heme cofactor induces conformational changes that rapidly propagate to the protein structure, an effect which is directly linked to the signal transduction mechanism. Interestingly, the two analyzed proteins have distinct levels of intrinsic disorder (25% for GSU0935 and 13% for GSU0582), which correlate with conformational stability differences. This provides evidence that the sensing threshold and intensity of the propagated allosteric effect is linked to the stability of the PAS-fold, as this property modulates domain swapping and dimerization. Analysis of the PAS-domain shows that disorder segments are found either at the hinge region that controls helix motions or in connecting segments of the β-sheet interface. The latter is known to be widely involved in both intra- and intermolecular interactions, supporting the view that it's folding and stability are at the basis of the specificity and regulation of many types of PAS-containing signaling proteins.